Effect of Nb Content on Strength and Toughness of 25MnB Crawler Steel and Its Microstructural Characterization - Zixun He; Jianjing Wang; Houxin Wang; Yajie Cui; Zhengbing Meng; Jiangbo Deng; Meiqiao Wu; Chaoyang Zhou; Xinbin Liu (Metals)
To address the failure of 25MnB crawler track steel due to insufficient strength and toughness, this study designed a new type of 25MnB crawler track steel and investigated the effects of the Nb content on its mechanical properties, microstructure, dislocation evolution, and precipitation behavior. The experimental results show that, compared to 25MnB steel without Nb, the addition of 0.03% Nb significantly increased the yield strength of the experimental steel to 1450 MPa, with an elongation rate of 15.9%. The room-temperature impact energy showed a slight improvement, while the low-temperature impact absorption energy improved notably, reaching 36 J at −40 °C. The microstructural characterization and analysis revealed that increasing the Nb content refined the effective grain size of prior austenite and martensite. The (Nb, Ti)C precipitates provided a higher precipitation driving force, promoting the formation of precipitates and increasing the average dislocation density. Additionally, the increased proportion of high-angle grain boundaries (HAGBs) enabled grain boundaries and precipitates to jointly hinder crack propagation. This study demonstrates that Nb-Ti microalloying can effectively enhance the strength, toughness, and plasticity of track steel, demonstrating promising application prospects.